Newborn Sickle Cell and Thalassaemia Screening Programme: Automating and Enhancing the System to Evaluate the Screening Programme - Catherine Coppinger; Robyn O'Loughlin (MDPI AG, 2019)
Good information is needed to demonstrate that a screening programme is meeting its objectives, to measure performance against standards and to ensure that action is taken if standards are not met. In 2010, the NHS Sickle Cell and Thalassaemia (SCT) Screening Programme established a process to collect data on the main outcome measures for newborn babies. In 2016, a review identified that data completeness and quality relied on manual processes and there was widespread dissatisfaction amongst data providers due to duplication of data entry, poor feedback and lack of oversight of the baby to ensure safe handover from screening into treatment services. Using an Agile service design process and following the Government Digital Service Model, the SCT Screening Programme worked in close collaboration with users, wider stakeholders and system suppliers to design and build a new automated system. The new system ensures that the screening programme can fulfil its duty to evaluate the effectiveness of the programme, whilst pleasing the users and enhancing safety. User experience must be central to design and ongoing development to ensure that a new IT system is fit for purpose and adopted by users.